Evaluation of Canine Pancreas‐Specific Lipase Activity, Lipase Activity, and Trypsin‐Like Immunoreactivity in an Experimental Model of Acute Kidney Injury in Dogs. (17th December 2015) - Hulsebosch, S.E.; Palm, C.A.; Segev, G.; Cowgill, L.D.; Kass, P.H.; Marks, S.L.
Abstract : Background: Diagnosis of pancreatitis in dogs is complicated by extrapancreatic disorders that can alter the results of laboratory tests. Extrapancreatic disorders can also affect the diagnosis of exocrine pancreatic insufficiency (EPI). The effects of acute kidney injury (AKI) on pancreas‐specific lipase activity (Spec cPL ® Test), serum lipase activity and trypsin‐like immunoreactivity (TLI) in dogs have not been evaluated. Hypothesis/Objectives: Serum Spec cPL, lipase activity, and TLI concentrations will increase secondary to decreased kidney function. Animals: Five purpose‐bred dogs. Methods: Experimental prospective study. Gentamicin was used to induce AKI in 5 purpose‐bred dogs. Serum samples were collected for measurement of creatinine, Spec cPL, lipase activity and TLI over 60 days, during both induction of, and recovery from, AKI. Results: All dogs developed and recovered from AKI. Six of 52 (12%) serum Spec cPL concentrations were increased (2 in the equivocal zone and 4 consistent with pancreatitis) in 2 of 5 (40%) dogs. Two of 51 (4%) serum lipase activity values were increased in 2 of 5 dogs. Serum TLI was increased above the reference range in 17 of 50 (34%) samples in 3 of 5 dogs. For all biomarkers, there was no consistent correlation with increases in serum creatinine concentration. Conclusions and Clinical Importance: Decreased renal excretion during experimental AKI did not cause consistent and correlated increases in serum Spec cPL, lipase activity, or TLI in this cohort of dogs.